Efikasi Diri dan Self-Care pada Pasien Sindrom Koroner Akut - Ode Irman; Yohanes Paulus Pati Rangga (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Acute Coronary Syndrome (ACS) is a medical emergency that is still a major cause of global morbidity and mortality. The success of ACS treatment and prevention of recurrence is highly dependent on self-care. However, many ACS patients have difficulty performing self-care due to low self-efficacy. This study aims to explain the relationship between self-efficacy and self-care in ACS patients. This study used a correlation analytic design with a cross-sectional approach. The study population was 62 outpatients at the Heart Clinic, with a sample of 41 people selected using purposive sampling. Self-efficacy was measured using the Cardiac Self-Efficacy Scale (CSE scale) and self-care using the Self-Care of Coronary Heart Disease Inventory (SC-CHDI). The study was conducted in April-May 2025. Data were analyzed using the Pearson product moment correlation test. The results showed a p value of 0.004 (p <α), which means there is a relationship between self-efficacy and self-care in ACS patients. The direction of the relationship is positive, meaning that the higher the self-efficacy, the better the self-care, and vice versa with the closeness of the relationship in the weak category (r 0.437). Self-efficacy is positively related to better self-care behavior in ACS patients. Therefore, nurses can integrate self-care improvement care through comprehensive self-efficacy education.